Steady and unsteady state peritectic solidification. (January 2015) - Castanho, M. A. P.; Goulart, P. R.; Brito, C.; Spinelli, J. E.; Cheung, N.; Garcia, A.
<x content-type="archive" xml:space="preserve">Abstract</x> In the present study, Pb–Bi as a model of alloys from peritectic systems was directionally solidified under transient heat flow conditions, which is the class of heat flow encompassing the majority of industrial solidification processes. Some experiments were also carried out in a vertical tube furnace under cooling rates closer to equilibrium during solidification in order to broaden the range of solidification parameters. Thermal parameters such as the tip growth rate (VL) and the cooling rate <inline-graphic xlink:href="ark:/27927/pgh2bv7gn0v" xmlns:xlink="http://www.w3.org/1999/xlink" /> were experimentally determined and correlated with the primary (λ1) and secondary (λ2) dendrite arm spacings by experimental growth laws. It is shown that the proposed growth laws are able to encompass also the growth of dendritic branches during steady state growth from the melt.